Building implementable marketing models - Naert, P. A.; Leeflang, P. S. H. (Leiden ; Boston : Martinus Nijhoff Social Sciences Division ; Hingham, Mass. : distributed by Kluwer Boston, 1978)
The text is deals with models or management science in marketing courses.
Includes bibliography and index
kjo 16/01/2019
Loans
Keywords: Marketing; Marketing models; Management science